Gambaran Tingkat Kepatuhan Terapi Insulin Pada Penderita Diabetes Melitus Tipe 2 Di Rumah Sakit Cut Meutia Aceh Utara - Nihaayah Elzan, Chika; Sawitri, Harvina; Surayya, Rahmi (Jurnal Ilmiah Manusia Dan Kesehatan, 2025)
Diabetes mellitus (DM) is a metabolic endocrine disease characterized by chronically elevated blood glucose levels. One of the management of diabetes mellitus is using insulin therapy. Insulin therapy aims to maintain blood sugar control targets. Therefore, it is important to maintain compliance in undergoing insulin therapy to avoid complications and get the desired therapy results. The purpose of this study was to describe the level of compliance with insulin therapy for type 2 diabetes mellitus patients at Cut Meutia Hospital, North Aceh. This research is an observational study with descriptive methods and a cross-sectional approach. Research sampling with purposive sampling with a total of 105 respondents. Data were obtained using the Morisky Medication Adherence Scale (MMAS-8) questionnaire instrument. Based on the results of the study, 37.1% of respondents were the majority of early elderly (46-55 years), 51.4% of respondents were male, 28.6% of respondents had tertiary education, 46.7% of respondents did not work and 31.4% of the type of insulin used was insulin co-formulation. This study shows the level of compliance of type 2 DM patients in undergoing insulin therapy at Cut Meutia Hospital, North Aceh 42.9% with a high level of compliance, 44.8% with a moderate level of compliance and 12.4% with a low level of compliance. The reason for patient non-compliance in carrying out insulin therapy is mostly influenced by forgetting factors with a percentage of 56.2%. The conclusion of this study is the level of compliance of patients with type 2 diabetes mellitus at Cut Meutia Hospital, North Aceh in carrying out insulin therapy, the majority of respondents have a moderate level of compliance.